Distrito Paco the Philippine Transport Museum and PNR Railway Station - Bautista, Bryan Mikhail T.
Distrito Paco is an architectural thesis inspired by the memorandum of agreement between the PNR and the RIHSPI. It involves the architectural conservation of the old Paco train station, one of the most significant and remaining historic train stations in the country, to transport museum geared towards the support of Philippine transport heritage and transport culture. The design thesis seeks to bridge the architectural conservation of the old Paco train station, its adaptation into a transport museum and the redevelopment of the existing PNR Paco station through the conservation process and theories on new-old/architectural addition design. The project also includes Plaza Dilao as part of the architectural solution that promotes mass transit and highly pedestrianized city mobility. Overall, the goals of the study are to explore the possibilities of conservation of the old Paco train station, to develop a Philippine transport museum, including research on Philippine transport heritage, and to redevelop the existing PNR station based on the ridership goals of the PNR.